The Need for Modification: The Impact of COVID-19 on Pitch Competitions - Smith, Douglass; Muldoon, Jeffrey; Lakshmikanth, Geethalakshmi S. (Entrepreneurship education and pedagogy, 2022)
COVID-19 has had a dramatic impact on academics. Academic programs that require experiential learning, such as entrepreneurship, were presented with severe problems. At the time, the pandemic hit, Liguori and Winkler (2020) speculated on how entrepreneurship professors would respond to the challenge. Our article is an examination of how COVID-19 has impacted pitch competitions, a vital part of the entrepreneurship curriculum. We found that COVID-19 shut down pitch competitions for a year, and they returned last year using virtual web conferencing technologies such as Zoom. Our findings indicate that COVID-19 caused permanent changes to pitch competitions even though directors and other stakeholders may desire traditional face-to-face interactions.